Facilitators' delivery of a psychosocial intervention in a controlled trial for men with prostate cancer and their partners: a process evaluation. (8th February 2017) - Parahoo, Kader; McKenna, Suzanne; Prue, Gillian; McSorley, Oonagh; McCaughan, Eilis
Abstract: Aim: The aim of this paper was to report the process evaluation of facilitators' delivery of a psychosocial intervention (called CONNECT), in a randomized controlled trial, to men with prostate cancer and their partners. Background: There is a lack of information on the process of implementing psychosocial interventions in controlled trials and, in particular, on the role and performance of facilitators who deliver them. Yet, this information is crucial in assessing whether these interventions are effective or not and why. Design: Qualitative design. Methods: Semi‐structured qualitative interviews and diaries were used to collect data (January–October 2012) from four facilitators and a co‐facilitator. Data were analysed using the Miles et al . framework. Results: Five themes were discernible. These were 'difficulties to keep to the structure of the intervention', 'selective coverage of topics', 'partner participation', 'overall impression of the group and telephone sessions' and 'perceived benefits to participants'. Issues such as not keeping to the aim of the intervention, deviating from the content and/or reluctance in discussing sensitive issues such as sexual health may mean that the psychosocial effects of the intervention may not have been fully realized. Conclusions: These findings will be useful for further development and evaluation of the intervention. A tentative conceptual framework of factors, related to facilitators, influencing the fidelity of interventions in the context of controlled trials, is offered. This model, which requires further development and testing, will be useful for researchers worldwide who are involved in developing interventions and training facilitators.